Adult spinal deformities - Vialle, Luiz Roberto; Lenke, Lawrence G. 1960-; Cheung, Kenneth M.C (AOSpine masters series, 2015)
In this fourth volume of the AOSpine Masters Series experts from around the world share their strategies for managing the most common adult spinal deformities. This book gives clinicians the guidance they need to make the right treatment decisions and provide the best care for their patients. Chapter topics include osteotomies for rigid spinal deformities, postoperative coronal decompensation in adult deformity, and biomechanics and material science for deformity correction